IMPLEMENTASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DALAM MENERAPKAN BUDAYA RELIGIUS SISWA DI MA MAMBA’UL MA’ARIF DENANYAR JOMBANG - Khoirun Nisa'; Zuhrotul Farida (Center for the Research and the Communicator Service of IAI Hasanuddin Pare-Kediri, 2022)
ABSTRACT Education is a way of achieving the sciences to determine the future of civilization. A nation could be developed if education had the quality of students to print only competent students. However, their way of education is not without obstacles, problem such as moral degredation, and a decline in the value of ethics pose problems that should be answered by actors and educators. Therefore, the discourse that has made Indonesia the world leader is in line with that can be achieved in the forward sector. So, to answer the portrait of moral degredation, I offered some formulas that can be implemented with Islamic lerning in a adjusted religious culture. Religious culture is the habituation of releihous values that are applied consistently and continuously. The purpose of this research needs to know all religious cultures that are applied in MA Mamba’ul Ma’arif Denanyar Jombang and the method of that which is used in developing them as. It can be seen from any activity from every activity carried out there, starting from entering the class, repeating rote preceding the lesson started, and also when activities of Islam day celebration. Methods used to collect the data by means of observation, interviews and document using approach qualitative descriptive.